Peran Manajemen Data dan Database dalam Meningkatkan Efesiensi Operasional Perusahaan - Dinda Fitriyah Kholisoh Ahmadita Putri; Muhammad Irwan Padli Nasution (Asosiasi Riset Ilmu Manajemen Kewirausahaan dan Bisnis Indonesia, 2025)
In the digital era, companies are required to manage data optimally to improve operational efficiency. This research aims to analyze the role of data management and database systems in supporting company work efficiency. A descriptive approach is used by reviewing literature from various relevant academic sources. The results show that the implementation of a structured database system can reduce data redundancy, increase the speed of information access, and strengthen the decision-making process. With good data integration between divisions, the company can improve internal coordination and response to market changes. The findings confirm the importance of an effective data management strategy in supporting an organization's competitive advantage.